HUBUNGAN ANTARA KOMPETENSI GURU AL-QURAN HADIST DENGAN PRESTASI BELAJAR SISWA DIDIK MATA PELAJARAN AL-QURAN HADIST KELAS X MA MA’ARIF 10 SENDANG AGUNG - Rikki Ardiansyah (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2026)
The importance of the Qur’an and Hadith is so important for Muslims that education, especially in the subject of Al-Qur’an Hadith, is directed at providing provisions for students. can understand the Al-Quran and Hadith with its teaching elements. The ability to read the Al-Qur’an at MA Ma’arif 10 Sendang Agung is of sufficient value. namely 264, and the ability to write the Al-Qur’an at MA Ma’arif 10 Sendang Agung Rawi Penengahan is in the range of scores between poor and sufficient, namely 138. And the result of the combined score of both abilities to read and write the Al-Qur’an is that the highest score is 81 and the lowest score was 65. From these results it can be concluded that teachers of Al-Qur’an Hadith subjects not only prioritize students’ reading and writing of the Al-Qur’an, but also prioritize the results of material values ​​at school. The learning achievement of students at MA Ma’arif 10 Sendang Agung Rawi Penengahan is quite good, because seen from the results of the recapitulation of students’ final grades, the highest score is 81 and the lowest score is 74. From these findings it can be concluded that the learning achievement of MA Ma’arif students 10 Sendang Agung Rawi This mediation is good, but in terms of reading and writing the Qur’an it is slightly inferior.